2018
DOI: 10.1038/s41598-018-35925-z
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous toxins and the coupling of gregariousness to conspicuousness in Argidae and Pergidae sawflies

Abstract: Phytophagous insects tend to be either cryptic and solitary, or brightly colored and gregarious, as a defense against vertebrate predators. Here, we tested whether potent defensive chemicals produced de novo by larvae of Argidae and Pergidae sawflies have influenced the evolutionary relationship between larval appearance and levels of gregariousness. Phylogeny-based correlation analyses indicated only a weak trend for solitary species to be cryptic, and for gregarious ones to be conspicuous. Numerous Argidae w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“…Still another function is the visual impact of the body movements on predators hunting by sight and that can be frightened at distance 22 , especially when gregarious insects simultaneously raise their abdomens. Argidae and Pergidae larvae are commonly aggregated or truly gregarious, and grouped individuals are better defended than single ones against vertebrate and invertebrate predators 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Still another function is the visual impact of the body movements on predators hunting by sight and that can be frightened at distance 22 , especially when gregarious insects simultaneously raise their abdomens. Argidae and Pergidae larvae are commonly aggregated or truly gregarious, and grouped individuals are better defended than single ones against vertebrate and invertebrate predators 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Hepta- and octapeptides were isolated and identified from the sawfly species, and toxicological tests showed that they can kill vertebrates 5 , 8 . From an eco-evolutionary perspective, however, the toxic peptides that occur commonly among these two sawfly families were admittedly driven not by livestock but other organisms 9 , 10 .
Figure 1 Pictures showing larvae of most of the species used in the study.
…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Larvae of Argidae s.s. Feed on a diverse variety of angiosperms. Although the larvae of most argids remain unknown, they also present various degrees of gregariousness, chemical defence, feeding behaviour and morphological adaptations to their host plants (Smith, 1992;Schmidt et al, 2000;Boevé et al, 2018). Contrary to the known Pergidae and Argidae s.s., the larvae of Zenarge feed on gymnosperms, including the native Australian Callitris spp.…”
Section: Introductionmentioning
confidence: 99%